2013
DOI: 10.1080/11250003.2013.822025
|View full text |Cite
|
Sign up to set email alerts
|

Overview of life cycles in model species of the genusDugesia(Platyhelminthes: Tricladida)

Abstract: An overview of the reproductive patterns of seven model species of triclads belonging to the genus Dugesia from circum-Mediterranean and Afrotropical freshwater is provided. Populations can reproduce exclusively sexually or exclusively asexually by fissiparity but the coexistence of both reproductive modes is displayed by some lineages. The comparison of data on the life cycles as documented in the literature with new data highlights a wide array of potentialities to shift from an asexual to a sexual state and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In contrast, exfissiparous individuals of D. benazzii Lepori, 1951 andD. etrusca Benazzi, 1946 do not develop hyperplasic ovaries (Stocchino & Manconi, 2013).…”
Section: 1mentioning
confidence: 91%
“…In contrast, exfissiparous individuals of D. benazzii Lepori, 1951 andD. etrusca Benazzi, 1946 do not develop hyperplasic ovaries (Stocchino & Manconi, 2013).…”
Section: 1mentioning
confidence: 91%
“…Facultative reproduction in the genus Schmidtea involves the alternation of parthenogenesis and sexual reproduction [32], while facultative individuals of Dugesia alternate fissiparity with sex ([33], and references therein). It could be thought that triploid facultative Dugesia individuals may in fact alternate fission with parthenogenesis, due to the disadvantages of polyploids during meiotic processes [34].…”
Section: Introductionmentioning
confidence: 99%
“…Under certain conditions (mostly in the laboratory) triploid fissiparous planarians can develop hyperplasic ovaries and a copulatory apparatus [ 4 , 9 , 10 ], these individuals are known as ex-fissiparous. In D. sicula , it has been observed that some ex-fissiparous individuals laid cocoons but remained sterile [ 4 , 9 - 11 ], which indicated that asexual populations have lost the capability to sexually reproduce.…”
Section: Introductionmentioning
confidence: 99%